Sex Work and Drug Use in a Subculture of Violence - Surratt, Hilary L.; Inciardi, James A.; Kurtz, Steven P.; Kiley, Marion C. (Crime & delinquency, 2004)
This article examines the subculture of violence thesis as it relates to female street sex workers in Miami. Interview and focus group methods were used to study the intersections of childhood trauma, drug use, and violent victimization among 325 women. Using targeted sampling, crack- and heroin-using sex workers were recruited through street outreach into an HIV-prevention research program. Interviews used standard instrumentation and focused on drug-related and sexual risk for HIV, sex work, violence, childhood trauma, and health status. Nearly half of the respondents reported physical (44.9%) and/ or sexual (50.5%) abuse as children, and over 40% experienced violence from clients in the prior year: 24.9% were beaten, 12.9% were raped, and 13.8% were threatened with weapons. Consistent relationships between historical and current victimization suggest that female sex workers experience a continuing cycle of violence throughout their lives. The policy and research implications of these findings are discussed. [ABSTRACT FROM AUTHOR]